Mengukur Experiential Marketing dalam Dunia Virtual - Muhammad Rijal Fathurrahman; Popy Rufaidah (Jurnal Sosioteknologi, 2023)
The purpose of this study is to propose a measurement approach to measure the concept of virtual experiential marketing (VEM). This study offers a scale to measure VEM based on the theory of strategic experiential modules (SEMs) and telepresence. The study was conducted in a virtual world using a sample of 140 'Second Life' users. This study uses confirmatory factor analysis (CFA) to test how well the measured variables represent constructs. The results showed that all fit indices indicated that the VEM scale had six construct factors (Sense, Feel, Think, Act, Relate, and Telepresence); the results show that the model is complete and valid. This research is one of the first to investigate the measurement of virtual experiential marketing in virtual worlds.